2015
DOI: 10.25115/psye.v7i3.523
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Professional Development in Singapore: Depicting the Landscape

Abstract: ABTRACT: This article depicts the landscape of teacher professional development (PD) in Singapore, one of the world’s top-performing countries in education. We provide an overview of the resources available to the approximately 30,000 teachers within the 350 primary and secondary schools run by the Ministry of Education (MOE). We focus on the three main PD providers: the National Institute of Education, the Academy of Singapore Teachers and six Centers of Excellence, and schools themselves. Guided by the “Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 22 publications
1
32
0
5
Order By: Relevance
“…This lack of relationship suggests that formal PD, despite being perceived as relatively useful by preschool teachers, might also be perceived as being somewhat disconnected from the actual reality of the classroom. Contributing to this sense of disconnection might be that formal PD activities in Singapore are generally conducted outside the workplace (e.g., ECDA, tertiary institutions), and are led by external PD providers who might be not aware of the specific challenges and problems faced by teachers in their respective centers (Bautista, Wong et al, 2015). The fact that formal PD is often mandatory and planned following a top-down approach  not necessarily in response to teachers' motivations, interests, and needs  might be contributing to the lack of impact on teachers' self-efficacy beliefs (Desimone & Garet, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of relationship suggests that formal PD, despite being perceived as relatively useful by preschool teachers, might also be perceived as being somewhat disconnected from the actual reality of the classroom. Contributing to this sense of disconnection might be that formal PD activities in Singapore are generally conducted outside the workplace (e.g., ECDA, tertiary institutions), and are led by external PD providers who might be not aware of the specific challenges and problems faced by teachers in their respective centers (Bautista, Wong et al, 2015). The fact that formal PD is often mandatory and planned following a top-down approach  not necessarily in response to teachers' motivations, interests, and needs  might be contributing to the lack of impact on teachers' self-efficacy beliefs (Desimone & Garet, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wealth of PD resources available to Singapore teachers (Bautista, Wong, & Gopinathan, 2015), no published research has reported on the frequency with which preschool teachers participate in the different types of formal and informal PD activities. Similarly, no research has focused on exploring how preschool teachers themselves perceive the usefulness of the PD activities in which they participate.…”
Section: Goalsmentioning
confidence: 99%
“…The authors argue that Singapore's comprehensive set of PD resources, considered as a whole, presents the features of high-quality PD described in the literature. However, they suggest that more research is needed to examine the extent to which such ambitious PD model is enhancing teachers' practices and students' learning (Bautista, Wong, & Gopinathan, 2015).…”
Section: Singaporementioning
confidence: 99%
“…Este enfoque investigador, sin duda de orientación más pragmática o aplicada (Bautista, Wong, & Gopinathan, 2015), podría contribuir a una formación más completa e integral del profesorado, una formación que no se limite al dominio del instrumento o conceptos teóricos, sino que tenga siempre en cuenta los hallazgos de las investigaciones más recientes (Ponce de León & Lago, 2009). Está claro una enseñanza musical de calidad implica huir del nocivo e insano modelo de conservatorio y adoptar enfoque más constructivos (e.g., Bautista et al, 2010Bautista et al, , 2011Checa, 2004;López-Íñiguez et al, 2014;.…”
Section: Hacia Nuevas Metas Y Narrativas De Investigación En Educacióunclassified